Efektivitas Layanan Bimbingan Kelompok untuk Meningkatkan Pemahaman Praktik Kerja Industri (Prakerin) - Intan Khairunnisa; Nurmawati Nurmawati; Cici Yulia (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The problem of this research is based on the low understanding of industrial work practices (prakerin), students do not have the readiness to work both mentally and physically. This research aims to determine the effectiveness of group guidance services in increasing understanding of industrial work practices (prakerin) at Yappika Legok Vocational School. This research uses a pre-experimental quantitative method with a one-group pretest-posttest research design. The sample used was purposive sampling with 10 students from a population of 90. Validity test uses correlation test with product moment. The number of statement items was 25 items, then tested on 31 respondents, 25 valid items were 0 invalid items. Data analysis techniques used the Normality test, Homogeneity test, t test. The results of the research prove that there is an increase in understanding of industrial work practices (prakerin) at Yappika Legok Vocational School, as evidenced by the results of the hypothesis test, namely sig .000 < 0.05, so Ho and Ha are accepted. The conclusion is that there are differences in industrial work practices (prakerin) before and after being given treatment, group guidance services are effective in increasing understanding of industrial work practices (prakerin) at Vocational School Yappika Legok Kab. Tangerang.